Labor Market Efficiency in Indonesia: An Empirical Evidence from Household Survey - Prabowo, Tripitono Adi; Wulansari, Dyah; Sugiharti, Lilik (The journal of contemporary issues in business and government, 2021)
This paper aims to measure labor markets efficiency using production frontier framework. Using Household Social and Economic Survey run by Bureau Statistical Agency, we estimate the production frontier of human capital function in determining earnings. We estimate the model since 1998 until 2014 but with missing some years of observation those are 2004, 2005, and 2011. Wes estimate the on the basis cross section data and we compare them to other periods applying Corrected Ordinary Least Square (COLS), Corrected Median Absolute Deviation (CMAD), and Maximum Likelihood function for Stochastic Frontier Analysis (SFA). The results shows that all input variables are strongly significant with positive sign. All three methods of estimation results consistent parameters both in terms of values and signs. The efficiency scores of labor markets in Indonesia are relatively very low but have increasing pattern every year.